Parallel speciation or long‐distance dispersal? Lessons from seaweeds (Fucus) in the Baltic Sea. (17th July 2013) - Pereyra, R. T.; Huenchuñir, C.; Johansson, D.; Forslund, H.; Kautsky, L.; Jonsson, P. R.; Johannesson, K.
Abstract: Parallel evolution has been invoked as a forceful mechanism of ecotype and species formation in many animal taxa. However, parallelism may be difficult to separate from recently monophyletically diverged species that are likely to show complex genetic relationships as a result of considerable shared ancestral variation and secondary hybridization in local areas. Thus, species' degrees of reproductive isolation, barriers to dispersal and, in particular, limited capacities for long‐distance dispersal will affect demographical structures underlying mechanisms of divergent evolution. Here, we used nine microsatellite DNA markers to study intra‐ and interspecific genetic diversity of two recently diverged species of brown macroalgae, Fucus radicans (L. Bergström & L. Kautsky) and F .  vesiculosus (Linnaeus), in the Baltic Sea. We further performed biophysical modelling to identify likely connectivity patterns influencing the species' genetic structures. For each species, we found intraspecific contrasting patterns of clonality incidence and population structure. In addition, strong genetic differentiation between the two species within each locality supported the existence of two distinct evolutionary lineages ( F ST  = 0.15–0.41). However, overall genetic clustering analyses across both species' populations revealed that all populations from one region (Estonia) were more genetically similar to each other than to their own taxon from the other two regions (Sweden and Finland). Our data support a hypothesis of parallel speciation. Alternatively, Estonia may be the ancestral source of both species, but is presently isolated by oceanographic barriers to dispersal. Thus, a limited gene flow in combination with genetic drift could have shaped the seemingly parallel structure.